Impact of Education on Agricultural Operations: A Case study - Lakshman Chandra Pal (UIN Sunan Gunung Djati Bandung, 2023)
Agricultural activities as well as the system of agriculture anywhere in the world depend on a set of physical, socio-economic, and techno-institutional determinants. Among these, a farmer's education is very crucial in the process of production. Education plays a decisive role in adopting modern implements and technology in agriculture and, therefore, in the productivity of crops. The main objective of the paper is to analyze the relationship between the farmer’s level of education and agricultural operations, including the productivity of crops in the interfluves of the Mayurakshi and Bansloi rivers in Birbhum district, West Bengal, India. Data for the study have been collected from door-to-door surveys by making a suitable questionnaire. Pearson’s correlation has been used to show the relationship between the variables. The study shows that almost in all cases, there is a direct and positive relationship between the level of farmers' education and agricultural activities, especially in the application of farm inputs and the productivity of different crops.